Kompetensi Kepribadian Guru dalam Kitab Adab Al-‘Alim Wa Al Muta’alim dalam Perspektif Permendiknas No. 16 Tahun 2007 - Stamrotul Zakiah; Qurrotul Ainiyah (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2019)
Teacher's personality is a very important competency. The weak personality of the teacher can cause moral violations. Therefore it needs to be regulated in legislation, one of them is Permendiknas No 16 Th. 2007. The Book of Adab al-im alim Wa al-Muta'allim is one of the great works of Hadratus Syaikh Hasyim Asy'ary also explaining the teacher's personal competence. This study describes the teacher's personality competencies in the Permendiknas No 16 Th. 2007. The results of this study are expected to be a reference material to be able to improve teacher personality competencies. This is library research with a descriptive and comparative qualitative approach, using primary and secondary documentary data sources, which data are analyzed using comparative analysis. This study concludes that the study of teacher personality competencies in the book of Adab Alim wa al Muta'allim is explained in detail. The contents of these competencies are appropriate and cover the whole formulation of the core teacher’s personality competencies which are explained globally and generally in the Pemendiknas no. 16 of 2007.